Hybrid electrolytic capacitor and its manufacturing method

JP7639697B2Active Publication Date: 2025-03-05NIPPON CHEMI CON CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021565595
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-17
Filing Date
2020-12-15
Publication Date
2025-03-05
Estimated Expiration
2040-12-15

AI Technical Summary

Benefits of technology

【0024】 本発明のハイブリッド型電解コンデンサは、高い静電容量、低いESR、優れた高周波特性及び高い高温耐久性を示す。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639697000004
    Figure 0007639697000004
  • Figure 0007639697000005
    Figure 0007639697000005
  • Figure 0007639697000006
    Figure 0007639697000006
Patent Text Reader

Abstract

Provided is a hybrid electrolytic capacitor having a large capacitance, a low ESR, and superior high frequency characteristics and high-temperature endurance. A hybrid electrolytic capacitor 1 is provided with: a cathode 10 comprising a cathode substrate 11 made of valve metal, an oxide layer 12 provided on a surface of the cathode substrate 11, an inorganic conductive layer 13 provided on a surface of the oxide layer 12 and including an inorganic conductive material, and an organic conductive layer 14 provided on a surface of the inorganic conductive layer 13 and including a conductive polymer; an anode 20 including an anode substrate 21 made of valve metal and a dielectric layer 22 provided on a surface of the anode substrate; and a composite electrolyte layer 30 including a solid electrolyte layer 31 provided between the organic conductive layer 14 of the cathode 10 and the dielectric layer 22 of the anode 20 and comprising conductive polymer particles 31a in contact therewith, and an electrolytic solution 32 filling gaps between the conductive polymer particles 31a in the solid electrolyte layer 31.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hybrid electrolytic capacitor including a composite electrolyte layer having a solid electrolyte layer containing a conductive polymer and an electrolyte solution impregnated into gaps in the solid electrolyte layer, and a method for manufacturing the same. [Background technology]

[0002] As electronic devices become smaller and faster, capacitors used in power circuits, etc. are required to have high capacitance, low equivalent series resistance (hereinafter, equivalent series resistance is abbreviated as "ESR"), excellent high frequency characteristics, and high high temperature durability. Among electrolytic capacitors equipped with an anode in which an oxide film is provided as a dielectric on the surface of a substrate made of valve metals such as aluminum, tantalum, niobium, etc. and subjected to surface enlargement treatment, an electrolyte that is in contact with the oxide film and acts as a true cathode, and a cathode (apparent cathode) made of a valve metal in contact with the electrolyte, a solid electrolytic capacitor using a conductive polymer with high conductivity and high thermal decomposition temperature derived from a monomer having a π-conjugated double bond such as substituted or unsubstituted thiophene, pyrrole, aniline, etc. as an electrolyte is suitable for meeting the above requirements. However, the above solid electrolytic capacitor has a problem that the defective parts of the oxide film as a dielectric are poorly repaired, and the leakage current gradually increases. In order to solve this problem, a so-called hybrid electrolytic capacitor has been proposed, in which the gaps in the solid electrolyte layer are impregnated with an electrolyte solution that has excellent oxide film repair properties. Hereinafter, an electrolytic capacitor having an electrolyte layer made only of conductive polymers will be referred to as a "solid electrolyte capacitor," and an electrolytic capacitor equipped with a composite electrolyte layer that has a solid electrolyte layer containing a conductive polymer and an electrolyte solution impregnated in the gaps in this solid electrolyte layer will be referred to as a "hybrid electrolyte capacitor."

[0003] For example, Patent Document 1 (JP Patent Publication No. 11-186110) discloses a hybrid electrolytic capacitor obtained by forming a conductive polymer layer in a capacitor element formed by winding an anode chemically processed foil and a counter cathode foil with a separator therebetween, and then impregnating the electrolytic solution, and in this document, the conductive polymer layer is formed by chemical polymerization. It is also shown that the leakage current of this hybrid electrolytic capacitor is significantly smaller both before and after a high-temperature load test at 105°C for 1000 hours than that of a solid electrolytic capacitor having an electrolyte layer made only of conductive polymer. In addition, Patent Document 2 (JP Patent Publication No. 2008-010657) discloses a hybrid electrolytic capacitor obtained by impregnating a capacitor element formed by winding an anode foil with a dielectric oxide film and a counter cathode foil with a separator therebetween with a dispersion containing conductive polymer particles and a solvent, drying the resulting conductive polymer layer, and then impregnating the gaps in the conductive polymer layer with an electrolyte. It has also been shown that the leakage current of this hybrid electrolytic capacitor is much smaller than that of a hybrid electrolytic capacitor in which a conductive polymer layer is formed by chemical polymerization, and the reason for this is said to be that the conductive polymer does not penetrate into defects in the dielectric oxide film, but instead the electrolyte penetrates, enhancing the repair function of the dielectric oxide film.It has also been shown that in the hybrid electrolytic capacitor shown in this document, the particles of the conductive polymer penetrate into the etched pores of the anode, increasing the capacitance at a frequency of 120 Hz, and further reducing the ESR at a frequency of 100 kHz due to the impregnation of the electrolyte.

[0004] In a solid electrolytic capacitor, a natural oxide film is generally present on the surface of the cathode made of valve metal, even if no treatment to provide an oxide film is performed. Therefore, the capacitance (C) of a solid electrolytic capacitor is the composite capacitance of the anode capacitance (Ca) and the cathode capacitance (Cc), as shown in the following formula (1). Even if the anode capacitance is increased by etching, the capacitance of the capacitor will be smaller than the anode capacitance as long as the cathode has capacitance.

number

[0005] Therefore, in order to increase the cathode capacity of solid electrolytic capacitors, etching has been performed on the cathode valve metal foil. However, if etching is excessive, the surface of the valve metal foil dissolves at the same time, which prevents the increase in the surface area ratio, and an oxide film is easily formed on the surface of the valve metal foil, so there is a limit to how much the cathode capacity can be increased and maintained by etching. Therefore, a method has been proposed in which a film of a conductive material that is less likely to form an oxide film is formed on the surface of the cathode valve metal foil, thereby increasing the cathode capacity and suppressing the growth of the oxide film.

[0006] For example, Patent Document 3 (JP Patent Publication 2000-114109A) discloses a solid electrolytic capacitor equipped with a cathode foil in which a chemical conversion oxide film is formed on the surface of an etched valve metal foil, and then a film made of a metal nitride such as TiN, ZrN, or TaN, which is difficult to form an oxide film, is formed on the surface by a vapor deposition method. The vapor deposition of the metal nitride removes part of the chemical conversion oxide film, establishing electrical continuity between the metal nitride and the valve metal foil, so that the cathode capacity becomes infinite, and the capacity (C) of the capacitor expressed by the above formula becomes equal to the anode capacity (Ca) and reaches a maximum. Also known are solid electrolytic capacitors that use other materials instead of metal nitride coatings to achieve similar effects. For example, Patent Document 4 (JP 2005-109270 A) discloses a solid electrolytic capacitor equipped with a cathode foil on which a coating made of a metal carbide with low specific electrical resistance such as TiC, WC or ZrC is formed by a vapor deposition method. Patent Document 5 (JP 2006-190878 A) discloses a solid electrolytic capacitor equipped with a cathode in which a carbon coating is formed on the surface of a valve metal by a dry plating method such as ion plating. Patent Document 6 (JP 2007-095865 A) discloses a cathode foil on which a carbon coating is formed by a coating method.

[0007] In addition, in a hybrid electrolytic capacitor, the capacitance (C) of the capacitor is the composite capacitance of the anode capacitance (Ca) and the cathode capacitance (Cc) as shown in the above formula (1), so it has been proposed to make the cathode capacitance approach infinity and the capacitance (C) of the capacitor expressed by the above formula approach the anode capacitance (Ca) using the methods shown in Patent Documents 3 to 6. For example, Patent Document 7 (WO2016 / 174806A1) discloses a hybrid electrolytic capacitor equipped with a cathode foil on which an inorganic conductive layer containing an inorganic conductive material such as carbon, nickel, nickel nitride, nickel carbide, titanium, titanium nitride, or titanium carbide is formed by a deposition method or a coating method. In this document, when a solid electrolyte layer is formed between an anode foil and a cathode foil using a polymerization solution containing a raw material of a conductive polymer, the conductive polymer coating is too dense, so that the electrolyte does not easily spread over the surface of the anode foil, and the repairability of the damaged dielectric layer is poor. Therefore, the solid electrolyte layer is formed using a dispersion in which fine particles of a conductive polymer are dispersed in a dispersion medium, or a solution in which a conductive polymer is dissolved in a solvent. In addition, although the obtained solid electrolyte layer is homogeneous, highly flexible, and has excellent electrolyte retention, the adhesion between the solid electrolyte layer and the anode foil or the cathode foil is low, and in particular, when an electrolyte is used, the electrolyte penetrates between the inorganic conductive layer and the solid electrolyte layer, which tends to hinder contact, making it difficult to increase the capacity and reduce the ESR of the capacitor. Therefore, the adhesion between the solid electrolyte layer and the inorganic conductive layer is increased by roughening the surface of the cathode foil by etching or the like and then forming the inorganic conductive layer. The capacitance at a frequency of 120 Hz and the ESR at a frequency of 100 kHz of the obtained hybrid electrolytic capacitor were measured, and it was reported that a high capacitance and low ESR had been achieved in the capacitor. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-186110 [Patent Document 2] JP 2008-010657 A [Patent Document 3] JP 2000-114109 A [Patent Document 4] JP 2007-095865 A [Patent Document 5] JP 2006-190878 A [Patent Document 6] JP 2007-095865 A [Patent Document 7] WO2016 / 174806A1 Summary of the Invention [Problem to be solved by the invention]

[0009] According to the hybrid electrolytic capacitor, the problem of the increase in leakage current in the solid electrolytic capacitor is solved, and the capacitance of the capacitor is increased by providing an inorganic conductive layer on the cathode. However, the capacitance of the hybrid electrolytic capacitor has only been evaluated under the condition of a frequency of 120 Hz as shown in Patent Document 2 and Patent Document 7, and the evaluation in the high frequency range has been insufficient. Therefore, the inventors measured the capacitance at 20 kHz for a hybrid electrolytic capacitor having a configuration similar to that of the capacitor in Patent Document 7, which has a cathode having a titanium carbide film or a carbon deposition film as an inorganic conductive layer on an etched valve metal foil. It was found that all of the capacitors showed relatively low capacitance and should be improved. In addition, when the ESR of the above hybrid electrolytic capacitor was measured under the condition of frequencies of 20 kHz and 100 kHz, all of the capacitors showed relatively high ESR values, and after a high-temperature durability test, a significant increase in ESR was observed, and it was found that this should also be improved. On the other hand, as mentioned above, high capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability are also required for hybrid electrolytic capacitors.

[0010] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a hybrid electrolytic capacitor that can meet the above-mentioned requirements. [Means for solving the problem]

[0011] For the hybrid electrolytic capacitor in the prior art, which has a cathode in which an inorganic conductive layer is provided on a valve metal foil, the reason why high capacitance is achieved at a frequency of 120 Hz but not at a frequency of 20 kHz will be explained with reference to Figures 2 and 3. Figure 2 is a diagram illustrating the resistance and capacitance components at and near the cathode of a hybrid electrolytic capacitor having a configuration similar to that in the prior art, and Figure 3 is a diagram illustrating the configuration of an equivalent circuit of a hybrid electrolytic capacitor in the low-frequency and high-frequency regions. The capacitance of the capacitor indicated by C in the above formula (1) is indicated by the symbol Cap in Figure 3, and the capacitance of the anode indicated by Ca in the above formula (1) is indicated by C in Figure 3. AOX The capacitance of the anode, shown as Cc in the above formula (1), is shown as C in Figure 3. COX are indicated using the symbol

[0012] As shown in Figure 2, the hybrid electrolytic capacitor cathode and the circuit configuration near the cathode are connected in parallel with the interface resistance R IN , Cathode oxide film resistor R COX and anodizing film capacitance C COX In the low frequency region, the cathode oxide film resistor R COX is the interface resistance R IN Since the capacitance of the hybrid electrolytic capacitor is significantly larger than that of the anodized film, the equivalent circuit of the hybrid electrolytic capacitor can be simplified as shown in the left diagram of Figure 3. As a result, the capacitance of the capacitor is AOX This is almost equal to 1 / (ωC COX ) from R IN becomes larger, and C COX The equivalent circuit of the hybrid electrolytic capacitor is shown in the right diagram of Figure 3. As a result, the capacitance of the capacitor, Cap, is multiplied by the capacitance of the anodic oxide film, C AOX and the capacitance of the anodic oxide film C COXThe combined capacitance of the anodic oxide film is C AOX It becomes smaller.

[0013] Therefore, the inventors have determined the interface resistance R IN As a way to reduce the resistance of the cathode, in other words to obtain an equivalent circuit like that shown in the left diagram of Figure 3 even in the high frequency range, we investigated the use of a conductive polymer layer with low electrolyte permeability on top of the inorganic conductive layer of the cathode, which has not been used in previous hybrid electrolytic capacitors. COX is the interface resistance R IN It was confirmed that the region where the capacitance becomes significantly larger can be expanded to the high frequency region, and that high capacitance can be achieved even in the high frequency region, and further that the obtained capacitor exhibits low ESR both before and after a high temperature load test, thus completing the present invention. Moreover, it was found that the above-mentioned effects can be obtained regardless of the presence or absence of etching or the type of inorganic conductive layer.

[0014] Therefore, the present invention first provides a cathode having a cathode substrate made of a valve metal, an oxide layer made of an oxide of the valve metal provided on a surface of the cathode substrate, an inorganic conductive layer containing an inorganic conductive material provided on the surface of the oxide layer, and an organic conductive layer containing a conductive polymer provided on the surface of the inorganic conductive layer; an anode having an anode substrate made of a valve metal and a dielectric layer formed on a surface of the anode substrate and made of an oxide of the valve metal constituting the anode substrate; a composite electrolyte layer including a solid electrolyte layer including conductive polymer particles provided between the organic conductive layer of the cathode and the dielectric layer of the anode and in contact with them, and an electrolyte solution filled between the conductive polymer particles in the solid electrolyte layer; The present invention relates to a hybrid electrolytic capacitor comprising:

[0015] In the present invention, the cathode substrate may or may not have etching pits, and if etching pits are present, they may be tunnel pits or spongy pits, or may be through-type pits or residual-core type pits. The oxide layer provided on the surface of the cathode substrate may be a conversion oxide film or a natural oxide film.

[0016] The present invention is characterized in that an organic conductive layer containing a conductive polymer is provided on the cathode. The organic conductive layer is preferably dense, specifically, 1.15 to 1.80 g / cm 3 in the range of 1.20 to 1.80 g / cm 3 In particular, the range of 1.60 to 1.80 g / cm 3 The dense organic conductive layer is preferably in the range of 1.15 g / cm. When the dense organic conductive layer is in contact with the composite electrolyte layer, the hybrid electrolytic capacitor is preferably provided with high capacitance, low ESR, excellent high frequency characteristics, and high high temperature durability. 3 If the density is less than 1.80 g / cm3, the effect of the present invention is difficult to obtain. 3 It is difficult to manufacture a conductive polymer layer having a density exceeding 100%. The density of the dense organic conductive layer described above is higher than the density of the solid electrolyte layer in a state in which the electrolyte is held therein, and therefore most of the electrolyte in the composite electrolyte layer is held in the solid electrolyte layer.

[0017] The organic conductive layer in the cathode can be formed with good adhesion on the inorganic conductive layer by electrolytic polymerization using the components consisting of the cathode substrate, the oxide layer, and the inorganic conductive layer as a working electrode. Therefore, in a preferred embodiment of the present invention, the organic conductive layer is an electrolytically polymerized film. In this specification, the components consisting of the cathode substrate, the oxide layer, and the inorganic conductive layer are sometimes referred to as a "support," and the components consisting of the cathode substrate and the oxide layer are sometimes referred to as a "current collector."

[0018] On the other hand, the composite electrolyte layer can be obtained by a method similar to a conventional method, that is, a method in which a dispersion liquid containing conductive polymer particles and a dispersion medium is filled between the dielectric layer of the anode and the organic conductive layer of the cathode, and dried to form a solid electrolyte layer, and then the obtained solid electrolyte layer is impregnated with an electrolytic solution.

[0019] Thus, the present invention also provides a method for producing a method for the treatment of atopic dermatitis. a cathode forming step including a step of forming an inorganic conductive layer using an inorganic conductive material on a surface of an oxide layer made of an oxide of the valve metal provided on a surface of a cathode substrate made of a valve metal, and a step of forming an organic conductive layer containing a conductive polymer on the surface of the inorganic conductive layer through electrolytic polymerization of a monomer having a π-conjugated double bond; an anode forming step of forming a dielectric layer by oxidizing the surface of an anode substrate made of a valve metal; a composite electrolyte layer forming step including a step of forming a solid electrolyte layer by filling a dispersion liquid containing conductive polymer particles and a dispersion medium between the organic conductive layer of the cathode and the dielectric layer of the anode, and drying the liquid; and a step of impregnating the solid electrolyte layer with an electrolytic solution; The present invention relates to a method for producing a hybrid electrolytic capacitor, comprising the steps of: 3 An organic conductive layer having a density in this range can be suitably obtained by using an electrolytic polymerization solution containing a solvent consisting of 100 to 80 mass % water and 0 to 20 mass % organic solvent, a monomer having a π-conjugated double bond, and a supporting electrolyte.

[0020] There is no particular limitation on the type of conductive polymer in the organic conductive layer and the conductive polymer in the solid electrolyte layer, and a conductive polymer derived from a known monomer having a π-conjugated double bond can be used. Both may be the same type of polymer (polymer derived from the same monomer) or different types of polymer (polymer derived from different monomers), but it is preferable that both are poly(3,4-ethylenedioxythiophene) since particularly high conductivity and high temperature durability can be obtained.

[0021] As described above, the effects of the present invention can be obtained regardless of whether the cathode substrate is etched or not and regardless of the type of the inorganic conductive layer. However, it is preferable that the inorganic conductive material constituting the inorganic conductive layer is carbon, since the change in capacitance before and after the high-temperature load test is small both in the low-frequency region and the high-frequency region.

[0022] In addition, the applicant has disclosed, in PCT / JP2019 / 022741, which was unpublished at the time of filing the application on which the priority claim of this application is based, an electrode body used in the cathode of an electrolytic capacitor exhibiting good capacity, which comprises a cathode body made of a valve metal and having a surface expansion layer formed thereon, and a carbon layer formed on the surface expansion layer, and the boundary between the surface expansion layer and the carbon layer has an uneven shape, and has also disclosed, as a method for manufacturing an electrode body having suitable performance, a method in which a slurry containing carbon particles is applied to the surface of the cathode body, dried, and then a pressing process is performed. When this method is performed using an etched aluminum foil as a substrate, the pressing process can push the carbon particles into the etching pits of the aluminum foil, and the carbon particles can break through the oxide film on the aluminum foil to establish electrical conductivity between the carbon layer and the aluminum of the substrate.

[0023] Although PCT / JP2019 / 022741 describes in detail the performance of a wet electrolytic capacitor using the electrode body as a cathode, it does not describe the performance of the capacitor when the electrode body is applied to a hybrid electrolytic capacitor. The inventors used the electrode body having the above-mentioned preferable performance as a support for obtaining an organic conductive layer in the cathode by electrolytic polymerization, and evaluated the performance of the obtained hybrid electrolytic capacitor. It was found that the change in capacitance before and after a high-temperature load test was particularly small in both the low-frequency and high-frequency regions. Therefore, in a particularly preferred embodiment of the hybrid electrolytic capacitor of the present invention, the cathode substrate has an etching pit, the inorganic conductive layer is a carbon coating layer containing carbon particles, and the carbon coating layer has an intrusion portion that penetrates into the etching pit and a penetration portion that penetrates the oxide layer and is conductive with the cathode substrate. Effect of the Invention

[0024] The hybrid electrolytic capacitor of the present invention exhibits high capacitance, low ESR, excellent high frequency characteristics and high high temperature durability. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a conceptual diagram illustrating a configuration of a hybrid electrolytic capacitor according to the present invention. [Diagram 2] FIG. 1 is a diagram illustrating the resistance component and the capacitance component at the cathode and in the vicinity of the cathode of a hybrid electrolytic capacitor according to the prior art. [Diagram 3] FIG. 1 is a diagram illustrating the configuration of an equivalent circuit in a low-frequency region and a high-frequency region in a hybrid electrolytic capacitor according to a prior art. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The configuration of the hybrid electrolytic capacitor of the present invention is shown in Fig. 1. The hybrid electrolytic capacitor 1 includes a cathode 10 having a cathode substrate 11 made of a valve metal, an oxide layer 12 made of an oxide of the valve metal provided on the surface of the cathode substrate 11, an inorganic conductive layer 13 containing an inorganic conductive material provided on the surface of the oxide layer 12, and an organic conductive layer 14 containing a conductive polymer provided on the surface of the inorganic conductive layer 13, an anode 20 having an anode substrate 21 made of a valve metal, and a dielectric layer 22 made of an oxide of the valve metal constituting the anode substrate provided on the surface of the anode substrate 21, a solid electrolyte layer 31 including conductive polymer particles 31a provided between the organic conductive layer 14 of the cathode 10 and the dielectric layer 22 of the anode 20 and in contact with them, and a composite electrolyte layer 30 including an electrolyte solution 32 filled between the conductive polymer particles 31a in the solid electrolyte layer 31.

[0027] The organic conductive layer 14 containing a conductive polymer in the cathode 10 is preferably dense. Specifically, the density of the organic conductive layer 14 is 1.15 to 1.80 g / cm. 3 Density in the range of 1.20 to 1.80 g / cm 3 In particular, the range of 1.60 to 1.80 g / cm 3 When this dense organic conductive layer 14 is in contact with the composite electrolyte layer 30, the hybrid electrolytic capacitor 1 is provided with high capacitance, low ESR, excellent high frequency characteristics, and high high temperature durability. When the density of the organic conductive layer 14 in the cathode 10 is 1.15 g / cm 3 If the density is less than 1.80 g / cm3, the effect of the present invention is difficult to obtain. 3 It is difficult to fabricate a conductive polymer layer having a thickness greater than 100 nm.

[0028] The hybrid electrolytic capacitor of the present invention can be produced by a method including a cathode forming step, an anode forming step, and a composite electrolyte layer forming step, which will be described below. Each step will be described in detail below.

[0029] (1) Cathode formation process The cathode formation step includes a step of forming an inorganic conductive layer using an inorganic conductive material on the surface of an oxide layer made of an oxide of the valve metal provided on the surface of a cathode substrate made of a valve metal, and a step of forming an organic conductive layer containing a conductive polymer on the surface of the inorganic conductive layer through electrolytic polymerization of a monomer having a π-conjugated double bond.

[0030] The cathode substrate may be a substrate made of a valve metal, which is used as a cathode substrate in a conventional hybrid electrolytic capacitor, without any particular limitation. For example, a foil made of a valve metal such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, or antimony may be used, and aluminum foil is particularly preferred. As the cathode substrate, these foils may be used in the form of a so-called plain foil without being subjected to an etching treatment, or foils whose surface area has been increased by subjecting them to a chemical or electrochemical etching treatment may be used. The etching pits in the cathode substrate may be tunnel pits or spongy pits, or may be through-type pits or residual core-type pits, and are appropriately selected according to the application of the hybrid electrolytic capacitor. These etching pits may be formed using known AC electrolysis and DC electrolysis.

[0031] The oxide layer provided on the surface of the cathode substrate may be a natural oxide film that is generally present on the surface of the cathode substrate. In addition, a chemical conversion oxide film may be formed on the surface of the cathode substrate by a chemical conversion treatment using a chemical conversion liquid such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate, and this chemical conversion oxide film may be used as the oxide layer.

[0032] First, an inorganic conductive layer is formed on the surface of the oxide layer using an inorganic conductive material to obtain a support. The inorganic conductive layer may be one layer, or two or more inorganic conductive layers may be formed using different inorganic conductive materials. There is no particular limitation on the type of inorganic conductive material forming the inorganic conductive layer and the method of forming the inorganic conductive layer, as long as sufficient adhesion with the oxide layer in the cathode can be ensured and an organic conductive layer can be formed on the surface of the inorganic conductive layer with good adhesion in the next stage. For example, an inorganic conductive layer can be provided by laminating inorganic conductive materials such as carbon, titanium, platinum, gold, silver, cobalt, nickel, and iron on the oxide film by means of vacuum deposition, sputtering, ion plating, coating, electrolytic plating, electroless plating, and the like. It is preferable to use carbon as the inorganic conductive material, since the change in electrostatic capacitance before and after a high-temperature load test is small both in the low-frequency region and the high-frequency region.

[0033] In a particularly preferred embodiment of the cathode, the cathode substrate has etching pits, and the inorganic conductive layer is a carbon coating layer containing carbon particles, and the carbon coating layer has an entry portion that enters the etching pit and a penetration portion that penetrates the oxide layer and is electrically connected to the cathode substrate. This particularly preferred inorganic conductive layer can be formed by carrying out a coating step of forming a slurry layer by coating a carbon slurry containing carbon particles on the surface of the oxide layer and drying it, and a pressing step of pressing the slurry layer to press the carbon particles into the etching pits of the cathode substrate and cause the carbon particles to break through the oxide layer.

[0034] The carbon slurry used in the coating step contains at least carbon particles, a binder, and a dispersion medium. Carbon particles having various shapes such as fibrous, spherical, and scaly can be used without any particular limitation, and examples thereof include porous carbon such as carbon nanotubes, carbon nanofibers, carbon nanohorns, and activated carbon, carbon black such as Ketjen Black, furnace black, channel black, and acetylene black, amorphous carbon, natural graphite, artificial graphite, graphitized Ketjen Black, and mesoporous carbon. These carbon particles may be used alone or in combination of two or more. However, the carbon slurry for forming a carbon coating layer having an intrusion portion that intrudes into the etching pit naturally contains at least carbon particles having a particle size that can intrude into the etching pit of the cathode substrate. In a preferred embodiment, the carbon slurry further contains carbon particles having a particle size that cannot intrude into the etching pit of the cathode substrate. In this preferred embodiment, the carbon particles may be composed of the same type of carbon, in other words, the same type of carbon having a wide particle size distribution, such as acetylene black having a wide particle size distribution, may be used, or a mixture of different types of carbon, such as a mixture of flake graphite and acetylene black, may be used to obtain a wide particle size distribution of the carbon particles.

[0035] As the binder, known binders such as polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, carboxymethyl cellulose, styrene butadiene rubber, etc. can be used alone or in combination of two or more. As the dispersion medium, any dispersion medium that does not adversely affect other components, such as N-methylpyrrolidone, dimethylformamide, tetrahydrofuran, isopropyl alcohol, water, etc., can be used without any particular limitation.

[0036] There is no particular limitation on the method of wet mixing the carbon particles, binder, and dispersion medium to obtain the carbon slurry, and the method may be manual mixing using a mortar, or may be performed using a known mixing device such as a stirrer, homogenizer, etc. There is no particular limitation on the mixing time as long as a uniform carbon slurry is obtained.

[0037] The obtained carbon slurry is applied to the surface of the oxide layer provided on the surface of the cathode substrate by a known application method such as a doctor blade method or a casting method under normal pressure or reduced pressure, and then dried to form a slurry layer. Next, a pressing step is performed in which pressure is applied to the obtained slurry layer.

[0038] Before applying the carbon slurry, a base layer made of a conductive inorganic material such as carbon, titanium nitride, or titanium carbide may be provided on the surface of the oxide layer by a deposition method such as vacuum deposition or ion plating. The base layer formed by the deposition method is formed only on the surface of the oxide layer on the outer surface of the cathode substrate, and is not formed on the surface of the oxide layer on the surfaces of the etching pits.

[0039] The pressing step can be performed by a roll press or a vertical press, and requires applying pressure to press the carbon particles into the etching pits of the cathode substrate and to make the carbon particles break through the oxide layer. If a base layer is provided on the outer surface of the cathode substrate, it requires applying pressure to make the carbon particles break through the base layer and the oxide layer. The pressure in the pressing step is set to a pressure of 1000 MPa when the interface resistance of the support is 10 mΩ cm. 2 Less than 6mΩcm, preferably 2 Less than 3mΩcm, more preferably 2It is preferable that the interfacial resistance in the support is adjusted to be equal to or less than 1 / 5, preferably equal to or more than 1 / 4 of the average length of the etching pits in the carbon coating layer. Here, the "interfacial resistance in the support" means an interfacial resistance that is dependent on all interfaces included in the support, measured between the carbon coating layer and the cathode substrate, and can be obtained by a known measurement method, for example, by the following method. First, a support having a carbon coating layer with a thickness of 20 to 30 μm is formed. Next, a probe having an array of a plurality of measurement test needles for measuring the potential of the surface of the carbon coating layer at many positions and an array of application test needles for applying a current to the support provided around the array is brought into contact with the surface of the carbon coating layer, and a predetermined direct current is applied between the application test needles, and the potential generated on the surface of the carbon coating layer when the current is applied is measured at many positions by the measurement test needles, thereby obtaining an actual measurement value of the potential distribution. Next, a model formula is constructed in which the measured thickness of the current collector, the resistance of the current collector, and the thickness of the carbon coating layer are fixed values, and the resistance and interface resistance of the carbon coating layer are variables, and the potential distribution in the model formula is calculated while changing the variables. Then, the interface resistance when the calculated value of the potential distribution obtained from the model formula and the measured value of the potential distribution match is the "interface resistance in the support". An example of a suitable device for obtaining the interface resistance in the support is the electrode resistance measurement system RM2610 manufactured by HIOKI ELECTROCHEMICAL CO., LTD. The thickness of the carbon coating layer is not particularly limited as long as the entire surface of the oxide layer and the cathode base to be covered by the carbon coating layer are covered, and can be, for example, an average thickness of 0.5 to 30 μm. In the measurement method using the above-mentioned potential distribution, a carbon coating layer with a thickness of 20 to 30 μm is used, but the value of the interface resistance in the support obtained by pressing a thinner carbon coating layer with the same pressure is similar to the value of the interface resistance in the support provided with a carbon coating layer with a thickness of 20 to 30 μm.

[0040] When the carbon coating layer contains carbon particles having a particle size that makes it impossible for the carbon particles to enter the etching pits, the particles are substantially present in the region of the carbon coating layer except for the entry portion, and in the pressing step, the particles compress and deform the etching pits to favorably improve the adhesion between the carbon coating layer and the current collector in contact therewith, and favorably reduce the interface resistance between the carbon coating layer and the current collector, and also favorably press the carbon particles having a particle size that can enter the etching pits into the etching pits. On the other hand, the carbon particles having a particle size that can enter the etching pits are filled not only in the entry portion of the carbon coating layer, but also in the gaps between the large carbon particles that exist only in the region except for the entry portion, and are present throughout the carbon coating layer. When the carbon particles having a particle size that cannot enter the etching pits are made of flake graphite, the flake graphite particles are oriented so that their basal planes overlap each other, making it easy to compress and deform the etching pits and easy to break through the oxide layer and be electrically connected to the cathode base. Furthermore, when flake graphite and carbon black are used in combination, the carbon black is easily pushed into the etching pits and between the flake graphite, forming an inorganic conductive layer that is particularly dense, has excellent conductivity, and has excellent adhesion to the current collector.

[0041] Next, an organic conductive layer containing a conductive polymer is formed on the surface of the inorganic conductive layer. The organic conductive layer is preferably dense, and specifically has a density of 1.15 to 1.80 g / cm. 3 in the range of 1.20 to 1.80 g / cm 3 In particular, the range of 1.60 to 1.80 g / cm 3 It is preferable that the dense organic conductive layer has a density in the range of 100 to 2000. There are no particular limitations on the method for forming the dense organic conductive layer as long as the dense organic conductive layer has a density in this range. However, the dense organic conductive layer can be preferably obtained via electrolytic polymerization.

[0042] The electrolytic polymerization is carried out by introducing a support consisting of a cathode substrate, an oxide layer, and an inorganic conductive layer as a working electrode together with a counter electrode such as a platinum plate or a nickel plate into a polymerization solution containing at least a monomer, a supporting electrolyte, and a solvent, and applying a voltage between the working electrode and the counter electrode. During the electrolytic polymerization, anions released from the supporting electrolyte are contained in the conductive polymer layer as a dopant.

[0043] As the solvent for the electropolymerization solution, a solvent capable of dissolving the desired amount of monomer and supporting electrolyte and having no adverse effect on the electropolymerization can be used. 3 In order to obtain an organic conductive layer having a density in this range, it is preferable to use a solvent consisting of 100 to 80 mass % water and 0 to 20 mass % organic solvent (hereinafter, a solvent consisting of 100 to 80 mass % water and 0 to 20 mass % organic solvent will be referred to as a "water-rich solvent"). Examples of organic solvents that can be mixed with water include methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, acetone, tetrahydrofuran, and methyl acetate. The density of the organic conductive layer increases as the water content in the solvent increases, and when only water is used as the solvent, the density is 1.60 to 1.80 g / cm. 3 Particularly preferred organic conductive layers can be obtained having densities in the range of

[0044] As the monomer, any monomer having a π-conjugated double bond that has been used for the production of a conventional conductive polymer can be used without any particular limitation. Representative monomers are shown below. These monomers may be used alone or as a mixture of two or more kinds.

[0045] First, thiophene and thiophene derivatives, for example, 3-alkylthiophenes such as 3-methylthiophene and 3-ethylthiophene, 3,4-dialkylthiophenes such as 3,4-dimethylthiophene and 3,4-diethylthiophene, 3-alkoxythiophenes such as 3-methoxythiophene and 3-ethoxythiophene, 3,4-dialkoxythiophenes such as 3,4-dimethoxythiophene and 3,4-diethoxythiophene, 3,4-alkylenedioxythiophenes such as 3,4-methylenedioxythiophene, 3,4-ethylenedioxythiophene and 3,4-(1,2-propylenedioxy)thiophene, 3,4-alkyleneoxythiathiophenes such as thiophene, 3,4-methyleneoxythiathiophene, 3,4-ethyleneoxythiathiophene, and 3,4-(1,2-propyleneoxythia)thiophene; 3,4-alkylenedithiathiophenes such as 3,4-methylenedithiathiophene, 3,4-ethylenedithiathiophene, and 3,4-(1,2-propylenedithia)thiophene; and alkylthieno[3,4-b]thiophenes such as thieno[3,4-b]thiophene, isopropylthieno[3,4-b]thiophene, and t-butyl-thieno[3,4-b]thiophene.

[0046] Further examples include pyrrole and pyrrole derivatives, for example, N-alkylpyrroles such as N-methylpyrrole and N-ethylpyrrole, 3-alkylpyrroles such as 3-methylpyrrole and 3-ethylpyrrole, 3-alkoxypyrroles such as 3-methoxypyrrole and 3-ethoxypyrrole, 3,4-dialkylpyrroles such as N-phenylpyrrole, N-naphthylpyrrole, 3,4-dimethylpyrrole and 3,4-diethylpyrrole, and 3,4-dialkoxypyrroles such as 3,4-dimethoxypyrrole and 3,4-diethoxypyrrole. Further examples include aniline and aniline derivatives, such as 2,5-dialkylanilines such as 2,5-dimethylaniline and 2-methyl-5-ethylaniline, 2,5-dialkoxyanilines such as 2,5-dimethoxyaniline and 2-methoxy-5-ethoxyaniline, 2,3,5-trialkoxyanilines such as 2,3,5-trimethoxyaniline and 2,3,5-triethoxyaniline, 2,3,5,6-tetraalkoxyanilines such as 2,3,5,6-tetramethoxyaniline and 2,3,5,6-tetraethoxyaniline, and furan and furan derivatives, such as 3-alkylfurans such as 3-methylfuran and 3-ethylfuran, 3,4-dialkylfurans such as 3,4-dimethylfuran and 3,4-diethylfuran, 3-alkoxyfurans such as 3-methoxyfuran and 3-ethoxyfuran, and 3,4-dialkoxyfurans such as 3,4-dimethoxyfuran and 3,4-diethoxyfuran.

[0047] As the monomer, it is preferable to use a monomer selected from the group consisting of thiophenes having substituents at the 3rd and 4th positions. The substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the 3rd and 4th carbons. In particular, 3,4-(ethylenedioxythiophene) is preferable because it gives a conductive polymer that exhibits high conductivity and excellent heat resistance.

[0048] As the supporting electrolyte, any compound that releases a dopant contained in a conventional conductive polymer can be used without any particular limitation. For example, in addition to inorganic acids such as boric acid, nitric acid, phosphoric acid, and organic acids such as acetic acid, oxalic acid, and citric acid, sulfonic acids such as methanesulfonic acid, dodecylsulfonic acid, and p-toluenesulfonic acid, and salts thereof can be exemplified. In addition, polycarboxylic acids such as polyacrylic acid, polymethacrylic acid, and polymaleic acid, polysulfonic acids such as polystyrenesulfonic acid and polyvinylsulfonic acid, and salts thereof can also be used as the supporting electrolyte. Furthermore, boron complexes such as borodisalicylic acid, borodioxalic acid, and borodimalonic acid, sulfonylimic acid, and salts thereof can also be used as the supporting electrolyte. Examples of salts include alkali metal salts such as lithium salts, sodium salts, and potassium salts, and alkyl ammonium salts such as ammonium salts, ethylammonium salts, and butylammonium salts. Among them, at least one organic compound having no sulfonic acid group or sulfonate salt group and having an anion with a molecular weight of 200 or more, particularly borodisalicylic acid or its salts, and sulfonylimide acid and its salts, are preferred because they give conductive polymers with excellent heat resistance. These supporting electrolytes may be used alone or in combination of two or more, and are used in an amount not exceeding the saturation solubility in the polymerization solution and at a concentration at which a sufficient current for electrolytic polymerization can be obtained, depending on the type of supporting electrolyte.

[0049] In addition to the essential components of the monomer, supporting electrolyte, and solvent, the polymerization solution for electrolytic polymerization may contain other components that do not adversely affect the electrolytic polymerization, such as an anionic surfactant for solubilizing or emulsifying the monomer in the water-rich solvent. As the anionic surfactant, any anionic surfactant that is stable in the water-rich solvent can be used without any particular limitation. Representative anionic surfactants are shown below.

[0050] First, fatty acid salt surfactants, such as sodium laurate, sodium palmitate, and sodium stearate, can be mentioned. Next, amino acid surfactants, such as sodium lauroyl glutamate, sodium lauroyl aspartate, and sodium lauroyl methylalanine, can be mentioned. Next, sulfate ester surfactants, such as alkyl sulfate ester salts such as sodium dodecyl sulfate and sodium myristyl sulfate, and alkyl ether sulfate ester salts such as sodium polyoxyethylene lauryl ether sulfate and sodium polyoxyethylene alkyl ether sulfate. Next, sulfonic acid surfactants, such as alkane sulfonates such as sodium decane sulfonate and sodium dodecane sulfonate, alkyl benzene sulfonates such as sodium octyl benzene sulfonate and sodium dodecyl benzene sulfonate, alkyl naphthalene sulfonates such as sodium isopropyl naphthalene sulfonate and sodium butyl naphthalene sulfonate, polymeric sulfonates such as sodium polystyrene sulfonate, olefin sulfonates such as sodium tetradecene sulfonate, and sulfo fatty acid ester salts such as sodium dioctyl sulfosuccinate. Further examples include alkyl phosphate ester type surfactants, such as sodium lauryl phosphate, sodium myristyl phosphate, and polyoxyethylene sodium lauryl phosphate.

[0051] The anionic surfactant may be used alone or in a mixture of two or more kinds, and is used in an amount sufficient to solubilize or emulsify the monomer. If the anionic surfactant is a sulfonic acid surfactant and / or a sulfate ester surfactant, it is preferable because it leads to a hybrid electrolytic capacitor having excellent frequency characteristics.

[0052] The electrolytic polymerization is carried out by any of the methods of the constant potential method, the constant current method, and the potential sweep method. In the case of the constant potential method, although it depends on the type of monomer, a potential of 1.0 to 1.5 V against a saturated calomel electrode is suitable, and in the case of the constant current method, although it depends on the type of monomer, a potential of 1 to 10,000 μA / cm is suitable. 2 In the case of a potential sweep method, it is preferable to sweep the range of 0 to 1.5 V against a saturated calomel electrode at a rate of 5 to 200 mV / sec, although this depends on the type of monomer. There is no strict limit to the polymerization temperature, but it is generally in the range of 10 to 60°C. There is also no strict limit to the polymerization time, but it is generally in the range of 1 minute to 10 hours. The thickness of the organic conductive layer is generally in the range of 10 to 2000 nm, preferably 35 to 700 nm, and particularly preferably 70 to 350 nm.

[0053] The organic conductive layer after electrolytic polymerization is washed with water, ethanol, etc., and dried to obtain a cathode for the hybrid electrolytic capacitor of the present invention.

[0054] (2)Anode formation process In the anode formation step, the surface of the anode substrate made of a valve metal is oxidized to form a dielectric layer. As the anode substrate, a substrate made of a valve metal that is used as an anode substrate in a conventional solid electrolytic capacitor can be used without any particular limitation. For example, a foil made of a valve metal such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, or antimony, which has been subjected to a chemical or electrochemical etching process to increase the surface area, can be used, and aluminum foil is particularly preferred. The etching pits in the anode substrate may be tunnel pits or spongy pits, or may be through-type pits or residual core-type pits, and are appropriately selected according to the application of the hybrid electrolytic capacitor. These etching pits can be formed by known AC electrolysis and DC electrolysis. The dielectric layer on the surface of the anode substrate can be formed by a known method of subjecting the anode substrate to a chemical conversion treatment using a chemical conversion solution such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate.

[0055] (3) Composite electrolyte layer formation process The composite electrolyte layer forming step includes a step of forming a solid electrolyte layer by filling a dispersion liquid containing conductive polymer particles and a dispersion medium between the organic conductive layer of the cathode and the dielectric layer of the anode, and drying the dispersion liquid, and a step of impregnating the solid electrolyte layer with an electrolytic solution.

[0056] Usually, a separator is disposed between the organic conductive layer of the cathode and the dielectric layer of the anode, and the separator holds a solid electrolyte layer in contact with both the organic conductive layer of the cathode and the dielectric layer of the anode. For example, the above-mentioned belt-shaped cathode and anode are laminated with a separator between them so that the organic conductive layer of the cathode and the dielectric layer of the anode face each other, and then the laminate is rolled to form a capacitor element, after which a solid electrolyte layer can be formed. Also, the above-mentioned cathode and anode of a desired shape are laminated with a separator between them so that the organic conductive layer of the cathode and the dielectric layer of the anode face each other to form a capacitor element, and then a solid electrolyte layer can be formed. Also, a plurality of sets of cathodes and anodes are alternately laminated with a separator between them so that the organic conductive layer of the cathode and the dielectric layer of the anode face each other to form a capacitor element, and then a solid electrolyte layer can be formed. As the separator, a woven or nonwoven fabric made of cellulose-based fibers, for example, Manila paper, Kraft paper, Esparto paper, hemp paper, cotton paper, rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and the like, glass paper, and mixed papers of glass paper with Manila paper or Kraft paper can be used.

[0057] The solid electrolyte layer is formed by filling a dispersion liquid containing conductive polymer particles and a dispersion medium between the organic conductive layer of the cathode and the dielectric layer of the anode, and then drying the liquid. As the dispersion medium, a medium that does not dissolve or barely dissolves the conductive polymer particles contained in the dispersion liquid is selected and used, and water is particularly preferably used.

[0058] The dispersion liquid can be prepared, for example, by adding a monomer, an acid or its salt that releases a dopant, and an oxidizing agent to water as a dispersion medium, stirring until chemical oxidative polymerization is completed, and then removing the oxidizing agent and residual monomers by purification means such as ultrafiltration, cation exchange, and anion exchange, and then performing dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment as necessary. As the monomer, a monomer having a π-conjugated double bond as shown above for the organic conductive layer can be used, and a monomer selected from the group consisting of thiophenes having substituents at the 3rd and 4th positions can be preferably used. The substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbons at the 3rd and 4th positions. In particular, 3,4-(ethylenedioxythiophene) is preferred because it gives a conductive polymer that exhibits high conductivity and is also excellent in heat resistance. As the acid or its salt that releases a dopant, the compounds exemplified above as the supporting electrolyte can be used, and a compound that releases a polyanion, particularly polystyrene sulfonic acid or its salt, can be preferably used. As the oxidizing agent, a trivalent iron salt such as iron(III) p-toluenesulfonate, iron(III) naphthalenesulfonate, or iron(III) anthraquinonesulfonate, or a persulfate such as ammonium peroxodisulfate or sodium peroxodisulfate can be used.

[0059] Also, the above-mentioned monomer and the acid or its salt that releases the above-mentioned dopant are added to water as a dispersion medium, and electrolytic oxidation polymerization is performed while stirring. Then, residual monomers are removed by purification means such as ultrafiltration, cation exchange, and anion exchange, and then dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment are performed as necessary to obtain the above-mentioned polymer. Furthermore, the liquid obtained by the above-mentioned chemical oxidation polymerization method or electrolytic polymerization method is filtered to separate aggregates, thoroughly washed, and then added to water, and dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment are performed to obtain the above-mentioned polymer. The content of the conductive polymer particles in the dispersion is generally in the range of 1.0 to 3.0% by mass, and preferably in the range of 1.5 to 2.0% by mass. The particle size of the conductive polymer in the dispersion is generally in the range of 10 to 1000 nm. There is no strict limit to the drying temperature, but it is generally in the range of 50 to 200° C. There is also no strict limit to the drying time, but it is generally in the range of 1 to 10 hours.

[0060] The conductive polymer in the organic conductive layer of the cathode and the conductive polymer in the solid electrolyte layer may be derived from the same monomer or different monomers. As described above, it is preferable that the conductive polymer in the organic conductive layer is poly(3,4-ethylenedioxythiophene). However, it is preferable that the conductive polymer in the solid electrolyte layer is also poly(3,4-ethylenedioxythiophene), because particularly high conductivity and high temperature durability can be obtained.

[0061] Next, the obtained solid electrolyte layer is impregnated with an electrolyte solution under normal pressure or reduced pressure to form a composite electrolyte layer between the organic conductive layer of the cathode and the dielectric layer of the anode.

[0062] The electrolyte may be a known electrolyte that contains at least a solvent and a solute dissolved therein, and may be appropriately selected depending on the requirements of the hybrid electrolytic capacitor, such as the operating temperature. Examples of the electrolyte include γ-butyrolactone, δ-valerolactone, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, methyl cellosolve, ethylene glycol monomethyl ether, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, propylene carbonate, acetonitrile, water, or other solvents, and benzoates, butyrates, phthalates, isophthalates, terephthalates, salicylates, tartrates, oxalates, malonates, lysates, and lysates. An electrolyte solution containing a solute such as boronic acid salt, glutarate, adipate, azelaic acid salt, maleate, fumarate, citrate, pyromellitic acid salt, trimellitic acid salt, 1,6-decanedicarboxylate, formate, acetate, glycolate, lactate, 1-naphthoic acid salt, mandelate, citraconic acid, 2,4-dihydroxybenzoate, 2,5-dihydroxybenzoate, 2,6-dihydroxybenzoate, borodisalicylate, borodisoxalate, borodimalonate, etc. can be used. Examples of salts include quaternary ammonium salts such as ammonium salts, tetramethylammonium salts, and triethylmethylammonium salts, quaternary amidinium salts such as ethyldimethylimidazolinium salts and tetramethylimidazolinium salts, and amine salts such as trimethylamine salts and triethylamine salts. The above solvents may be used alone or in combination of two or more. The above solutes may be used alone or in combination of two or more kinds.In addition to the above-mentioned solvents and solutes, these electrolyte solutions may contain known additives. For example, for the purpose of improving the voltage resistance of the capacitor, the electrolyte solution may contain phosphoric acid, phosphoric acid compounds such as phosphoric acid esters, boric acid compounds such as boric acid, sugar alcohols such as mannitol, complex compounds of boric acid and sugar alcohols, polyoxyalkylene polyols such as polyethylene glycol, polyglycerin, and polypropylene glycol. Furthermore, the electrolyte solution may contain nitro compounds such as nitrophenol, nitrobenzoic acid, nitroanisole, and nitrobenzyl alcohol for the purpose of absorbing hydrogen that is rapidly generated, particularly at high temperatures.

[0063] The capacitor element to which the composite electrolyte layer has been added is then housed in an exterior case and sealed to obtain the hybrid electrolytic capacitor of the present invention. As described above, in the hybrid electrolytic capacitor of the present invention, the organic conductive layer containing the conductive polymer in the cathode is in contact with the composite electrolyte layer, resulting in high capacitance, low ESR, excellent high frequency characteristics, and high high temperature durability. EXAMPLES

[0064] The present invention will be described with reference to the following examples, but the present invention is not limited to the following examples.

[0065] Example 1 An aluminum foil with sponge-like etching pits formed thereon was used as a cathode substrate for obtaining a cathode. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 5.0 V. fs A titanium carbide vapor deposition film was then formed on the surface of the chemical oxide film by arc ion plating to obtain a support having a titanium carbide vapor deposition film (inorganic conductive layer).

[0066] 50 mL of distilled water was introduced into a glass container and heated to 40°C. 0.021 M of 3,4-(ethylenedioxythiophene) (hereinafter, 3,4-(ethylenedioxythiophene) will be referred to as "EDOT" and poly(3,4-(ethylenedioxythiophene)) will be referred to as "PEDOT") and 0.08 M of ammonium borodisalicylate were added to this solution and stirred to obtain a polymerization solution for electropolymerization. Next, the support (working electrode) and 10 cm 2 A SUS mesh counter electrode with an area of ​​0.1 mA / cm was introduced. 2 After the polymerization, the working electrode was washed with water and then dried at 100° C. for 30 minutes to obtain a 35 nm thick film with a mass of about 1.6 g / cm. 3 A PEDOT layer (organic conductive layer) having a density of 0.1 mA / cm was formed on the inorganic conductive layer to obtain a cathode for a hybrid electrolytic capacitor. 2 Constant-current electrolytic polymerization under the above conditions was performed multiple times with different times, and the thickness of the PEDOT layer obtained in each experiment was measured using an atomic force microscope or a step gauge. The relational equation between the thickness of the PEDOT layer and the amount of charge was then derived, and the amount of charge in the electrolytic polymerization was converted into the thickness of the PEDOT layer using the derived relational equation.

[0067] An etched aluminum foil was used as the anode substrate to obtain the anode. This aluminum foil was subjected to chemical conversion treatment using an aqueous solution of ammonium adipate as the chemical conversion solution, and the surface of the aluminum foil was applied with a chemical conversion voltage of 47.3 V. fs A chemical oxide film (dielectric layer) was formed on the anode, and an anode for a hybrid electrolytic capacitor was obtained.

[0068] The anode and cathode were connected to terminals, and the anode dielectric layer and the cathode organic conductive layer were laminated and wound with a separator between them. The anode was then repaired and converted for 15 minutes using an aqueous solution of ammonium dihydrogen phosphate at an applied voltage of 40.5 V and 10 mA, and then dried at 105°C for 30 minutes to obtain a capacitor element.

[0069] Fine particles of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid were dispersed in a dispersion medium of water with 5% by mass of ethylene glycol to obtain a dispersion liquid for forming a solid electrolyte layer. The above capacitor element was impregnated with the obtained dispersion liquid under a pressure of 30 kPa for 120 seconds, and dried at 150°C for 30 minutes. This dispersion liquid impregnation and drying were repeated again to obtain a capacitor element with an added solid electrolyte layer.

[0070] An electrolyte solution was prepared by dissolving 5% by mass of ammonium borodisalicylate in ethylene glycol. A fixed amount of this electrolyte solution was dispensed onto the capacitor element to which the solid electrolyte layer had been added, allowing the electrolyte solution to be impregnated into the solid electrolyte layer, resulting in a capacitor element to which a composite electrolyte layer had been added. The resulting element was sealed in an exterior case to obtain a hybrid electrolytic capacitor with a diameter of 8 mm and a height of 10 mm.

[0071] The hybrid electrolytic capacitor thus obtained was subjected to aging treatment for 45 minutes under conditions of 115°C by applying a voltage of 28.2V, to obtain a hybrid electrolytic capacitor with a rated voltage of 25V. As the initial characteristics of the obtained capacitor, the capacitance at 120Hz and 20kHz and the ESR at 20kHz and 100kHz were measured under conditions of 20°C. Next, a high-temperature durability test was performed in which a DC voltage of 25V was applied for 4000 hours under high-temperature conditions of 150°C as a durability test, and then, as the characteristics after the durability test, the capacitance at 120Hz and 20kHz and the ESR at 20kHz and 100kHz were measured again under conditions of 20°C.

[0072] Example 2 The electrolytic polymerization solution used in Example 1 was used, and the current was 0.1 mA / cm 2 By performing constant current electrolytic polymerization for 2 minutes under the condition of 3 The procedure of Example 1 was repeated, except that a cathode having a PEDOT layer (organic conductive layer) having a density of 100 nm was obtained on the titanium carbide vapor-deposited film (inorganic conductive layer).

[0073] Example 3 The electrolytic polymerization solution used in Example 1 was used, and the current was 0.1 mA / cm 2 By performing constant current electrolytic polymerization for 4.5 minutes under the condition of 3 The procedure of Example 1 was repeated, except that a cathode having a PEDOT layer (organic conductive layer) having a density of 100 nm was obtained on the titanium carbide vapor-deposited film (inorganic conductive layer).

[0074] Example 4 The electrolytic polymerization solution used in Example 1 was used, and the current was 0.1 mA / cm 2 By performing constant current electrolytic polymerization for 10 minutes under the condition of 3 The procedure of Example 1 was repeated, except that a cathode having a PEDOT layer (organic conductive layer) having a density of 100 nm was obtained on the titanium carbide vapor-deposited film (inorganic conductive layer).

[0075] Comparative Example 1 An aluminum foil with sponge-like etching pits formed thereon was used as a cathode substrate for obtaining a cathode. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 3.0 V. fs A chemical conversion oxide film (oxide layer) was formed, and a cathode having neither an inorganic conductive layer nor an organic conductive layer was obtained. The procedure of Example 1 was repeated, except that the obtained cathode was used instead of the cathode in Example 1.

[0076] Comparative Example 2 An aluminum foil with sponge-like etching pits formed thereon was used as a cathode substrate for obtaining a cathode. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 5.0 V. fs A chemical conversion oxide film (oxide layer) of was formed. Next, a vapor deposition film of titanium carbide was formed on the surface of the chemical conversion oxide film by arc ion plating to obtain a cathode having a vapor deposition film of titanium carbide (inorganic conductive layer) and no organic conductive layer. The procedure of Example 1 was repeated, except that the obtained cathode was used instead of the cathode in Example 1.

[0077] Example 5 An aluminum foil without etching pits was used as a cathode substrate to obtain a cathode. In this example, a chemical oxide film was not formed, and a natural oxide film was used as the oxide layer. Next, instead of the titanium carbide vapor deposition film, a vapor deposition film made of carbon was formed on the surface of the natural oxide film by sputtering, to obtain a support having a carbon vapor deposition film (inorganic conductive layer).

[0078] The electrolytic polymerization solution used in Example 1 was added to the support and 10 cm 2 A SUS mesh counter electrode with an area of ​​0.1 mA / cm was introduced. 2 After the polymerization, the working electrode was washed with water and then dried at 100° C. for 30 minutes to obtain a 350 nm thick, approximately 1.6 g / cm 2 3 A PEDOT layer (organic conductive layer) having a density of 1000 nm was formed on the carbon vapor deposition film (inorganic conductive layer) to obtain a cathode for a hybrid electrolytic capacitor. The procedure of Example 1 was repeated, except that the obtained cathode was used instead of the cathode in Example 1.

[0079] Comparative Example 3 An aluminum foil having no etching pits was used as a cathode substrate for obtaining a cathode. In this example, a chemical oxide film was not formed, and a natural oxide film was used as an oxide layer. Next, instead of a titanium carbide vapor deposition film, a vapor deposition film made of carbon was formed on the surface of the natural oxide film by sputtering, to obtain a cathode having a carbon vapor deposition film (inorganic conductive layer) and no organic conductive layer. The procedure of Example 1 was repeated, except that the obtained cathode was used instead of the cathode in Example 1.

[0080] Example 6 An aluminum foil with sponge-like etching pits formed thereon was used as a cathode substrate for obtaining a cathode. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 1.2 V. fs A chemical oxide film (oxide layer) was formed.

[0081] The carbon particles used were flake graphite with an average particle size of 4.5 μm and acetylene black with an average primary particle size of 50 nm and an average secondary particle size of 0.3 μm. A mixture of these in a mass ratio of 75:25 was mixed with styrene butadiene rubber and an aqueous solution of sodium carboxymethylcellulose in a mass ratio of 84:10:6, and the mixture was dispersed with a stirrer to prepare a carbon slurry.

[0082] The obtained carbon slurry was applied onto the above-mentioned chemical oxide film and dried to form a slurry layer. A linear pressure of 5.38 kNcm was applied to this slurry layer. -1 A pressing process was performed using a roll press to obtain a support for a hybrid electrolytic capacitor having a carbon coating film (inorganic conductive layer) having a thickness of 1 μm. When the cross section of this support was observed using an SEM photograph, it was found that acetylene black had penetrated to a position approximately 1 / 3 of the length of the etching pit. In addition, the flake graphite was oriented so that the basal planes of the graphite overlapped with each other, and acetylene black was filled between the graphite. Furthermore, the carbon slurry was applied onto the carbon coating film of the support for the hybrid electrolytic capacitor and dried to prepare a confirmation support having a carbon coating film having a thickness of 20 μm. The interface resistance of this support was measured using an electrode resistance measurement system (manufactured by Hioki Electrochemical Co., Ltd., model number RM2610), and was found to be 1.78 mΩcm. 2 From this value, it was determined that the carbon coating film of the support for the hybrid electrolytic capacitor was electrically connected to the aluminum of the cathode substrate.

[0083] The electrolytic polymerization solution used in Example 1 was added to the support and 10 cm 2 A SUS mesh counter electrode with an area of ​​0.1 mA / cm was introduced. 2 After the polymerization, the working electrode was washed with water and then dried at 100° C. for 30 minutes to obtain a 350 nm thick, approximately 1.6 g / cm 2 3A PEDOT layer (organic conductive layer) having a density of 1000 nm was formed on the carbon coating film (inorganic conductive layer) to obtain a cathode for a hybrid electrolytic capacitor. The procedure of Example 1 was repeated, except that the obtained cathode was used instead of the cathode in Example 1.

[0084] Comparative Example 4 An aluminum foil with sponge-like etching pits formed thereon was used as a cathode substrate for obtaining a cathode. This aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and the surface of the aluminum foil was subjected to a chemical conversion voltage of 1.2 V. fs A chemical oxide film (oxide layer) of was formed. Then, a carbon coating film was formed in the same manner as in Example 6 to obtain a cathode having a carbon coating film (inorganic conductive layer) and no organic conductive layer formed thereon. The procedure of Example 1 was repeated, except that the obtained cathode was used instead of the cathode in Example 1.

[0085] Table 1 shows the capacitance values ​​at 20°C obtained for the hybrid electrolytic capacitors of Examples 1 to 6 and Comparative Examples 1 to 4, and Table 2 shows the ESR values ​​at 20°C obtained for the hybrid electrolytic capacitors of Examples 1 to 6 and Comparative Examples 1 to 4. [Table 1]

[0086] [Table 2]

[0087] First, the capacitance of the hybrid electrolytic capacitor shown in Table 1 will be considered. Patent Documents 3 to 7 have already shown that the inorganic conductive layer can be used to increase the capacitance of the capacitor by bringing the cathode capacitance closer to infinity, but the evaluations have been performed only under conditions of 120 Hz, and the capacitance in the high frequency range (20 kHz) has not been shown. As is clear from comparing the capacitance of the capacitor having the cathode with the titanium carbide vapor deposition film of Comparative Example 2 and the capacitor having the cathode with the carbon vapor deposition film of Comparative Example 3 with the capacitance of the capacitor having the cathode without the inorganic conductive layer of Comparative Example 1, the measures in the prior art certainly increase the capacitance at 120 Hz, but do not increase the capacitance in the high frequency range (20 kHz). In contrast, the capacitance of the capacitor having the cathode with the carbon coating film disclosed by the applicant in PCT / JP2019 / 022741 also increases in the high frequency range (20 kHz). This is due to the fact that the carbon coating film has an intrusion portion that penetrates into the etching pit and a penetration portion that penetrates the oxide layer and is conductive to the cathode base.

[0088] In contrast, when the capacitances of the capacitors of Examples 1 to 4, each having a cathode with a dense organic conductive layer containing a conductive polymer, are compared with the capacitance of the corresponding capacitor of Comparative Example 2, the capacitance of the capacitor of Example 5 with the capacitance of the corresponding capacitor of Comparative Example 3, and the capacitance of the capacitor of Example 6 with the capacitance of the corresponding capacitor of Comparative Example 4, it is clearly understood that the capacitances of the capacitors of the Examples are increased not only at 120 Hz but also at 20 kHz, regardless of the type of inorganic conductive layer of the cathode, regardless of whether the oxide layer is a chemical oxide film or a natural oxide film, and regardless of the presence or absence of etching pits in the cathode substrate. This is because the dense organic conductive layer containing a conductive polymer is provided on the cathode, so that the interfacial resistance between this organic conductive layer and the composite electrolyte layer can be reduced, and the cathode oxide film resistance R COX is the interface resistance R IN This is due to the fact that the area where the signal becomes significantly larger can now be extended into the high frequency range.

[0089] As can be seen from Table 1, the change in capacitance before and after the extremely severe high-temperature durability test at 150° C. for 4000 hours is small in both the low-frequency and high-frequency regions for the capacitors of Examples 1 to 6. The change in capacitance before and after the high-temperature durability test is improved more in the capacitor using a cathode in which the inorganic conductive layer is made of carbon than in the capacitor using a cathode in which the inorganic conductive layer is made of titanium carbide, and in particular, the capacitor of Example 6 equipped with a cathode having a carbon coating film showed excellent high-temperature durability.

[0090] Next, the ESR of the hybrid electrolytic capacitors shown in Table 2 will be examined. When the ESR of the capacitor with the cathode having the titanium carbide vapor deposition film of Comparative Example 2 and the capacitor with the cathode having the carbon vapor deposition film of Comparative Example 3 is compared with the ESR of the capacitor with the cathode without the inorganic conductive layer of Comparative Example 1, it is clear that in the inorganic conductive layer of the prior art, the ESR is increased not only at 20 kHz but also at 100 kHz, and the change in ESR before and after the high-temperature durability test is also large. This increase in the change in ESR before and after the high-temperature durability test due to the use of a cathode with an inorganic conductive layer but no organic conductive layer was also observed in the capacitor of Comparative Example 4.

[0091] However, as can be clearly understood by comparing the ESR of the capacitors of Examples 1 to 4, which are provided with a cathode having a dense organic conductive layer containing a conductive polymer, with the ESR of the capacitor of the corresponding Comparative Example 2, the ESR of the capacitor of Example 5 with the ESR of the capacitor of the corresponding Comparative Example 3, and the ESR of the capacitor of Example 6 with the ESR of the capacitor of the corresponding Comparative Example 4, the ESR of the capacitors of the Examples is significantly reduced not only at 20 kHz but also at 100 kHz, regardless of the type of inorganic conductive layer of the cathode, regardless of whether the oxide layer is a chemical conversion coating or a natural oxide coating, and regardless of the presence or absence of etching pits on the cathode substrate, and the change in ESR before and after the high-temperature durability test is also significantly suppressed. This is due to the fact that the interface resistance is reduced by providing a dense organic conductive layer with excellent adhesion to both the composite electrolyte layer and the inorganic conductive layer on the cathode, and further, this reduction in interface resistance is maintained even during the high-temperature durability test. [Industrial Applicability]

[0092] According to the present invention, a hybrid electrolytic capacitor having high capacitance, low ESR, excellent high frequency characteristics and high high temperature durability can be obtained. [Explanation of symbols]

[0093] 1 Hybrid electrolytic capacitor 10 cathode 11 Cathode substrate 12 Oxide layer 13 Inorganic conductive layer 14 Organic conductive layer 20 Anode 21 Anode substrate 22 Dielectric layer 30 Composite electrolyte layer 31 Solid electrolyte layer 31a Conductive polymer particles 32 Electrolyte

Claims

1. a cathode having a cathode substrate made of a valve metal, an oxide layer made of an oxide of the valve metal provided on a surface of the cathode substrate, an inorganic conductive layer containing an inorganic conductive material provided on the surface of the oxide layer, and an organic conductive layer containing a conductive polymer provided on the surface of the inorganic conductive layer; an anode having an anode substrate made of a valve metal and a dielectric layer made of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; a composite electrolyte layer including a solid electrolyte layer including conductive polymer particles provided between the organic conductive layer of the cathode and the dielectric layer of the anode and in contact with them, and an electrolyte solution filled between the conductive polymer particles in the solid electrolyte layer; Equipped with the organic conductive layer in the cathode has a density in the range of 1.15 to 1.80 g / cm 3 ; The solid electrolyte layer in the composite electrolyte layer is formed using a dispersion liquid containing particles of the conductive polymer and a dispersion medium. A hybrid electrolytic capacitor characterized by:

2. 2. The hybrid electrolytic capacitor according to claim 1, wherein the organic conductive layer in the cathode is an electrolytic polymerized film.

3. 3. The hybrid electrolytic capacitor according to claim 1, wherein the conductive polymer in the organic conductive layer of the cathode and the solid electrolyte layer of the composite electrolyte layer is poly(3,4-ethylenedioxythiophene).

4. 4. The hybrid electrolytic capacitor according to claim 1, wherein the inorganic conductive material constituting the inorganic conductive layer is carbon.

5. the cathode substrate has etch pits; the inorganic conductive layer is a carbon coating layer containing carbon particles, 5. The hybrid electrolytic capacitor according to claim 1, wherein the carbon coating layer has an intrusion portion that intrudes into the etching pit and a through portion that penetrates the oxide layer and is electrically connected to the cathode substrate.

6. a cathode forming step including a step of forming an inorganic conductive layer using an inorganic conductive material on a surface of an oxide layer made of an oxide of the valve metal provided on a surface of a cathode substrate made of a valve metal, and a step of forming an organic conductive layer containing a conductive polymer on the surface of the inorganic conductive layer through electrolytic polymerization of a monomer having a π-conjugated double bond; an anode forming step of forming a dielectric layer by oxidizing the surface of an anode substrate made of a valve metal; a composite electrolyte layer forming step including: filling a space between the organic conductive layer of the cathode and the dielectric layer of the anode with a dispersion liquid containing conductive polymer particles and a dispersion medium, and drying the space; and impregnating the solid electrolyte layer with an electrolyte solution; Including, The density of the organic conductive layer is in the range of 1.15 to 1.80 g / cm 3 .

4. A method for producing a hybrid electrolytic capacitor comprising the steps of:

Citation Information

Patent Citations

  • Electrolytic capacitor and production thereof

    JP1995283086A

  • Electrolytic capacitor and manufacture thereof

    JP1999186110A

  • Solid electrolytic capacitor and its manufacture

    JP2000114109A

  • Solid electrolytic capacitor and its manufacturing method

    JP2001196270A

  • Manufacturing method of electrode metal material and manufacturing method of capacitor using the same

    JP2001297952A